Pathological mandibular fracture associated with diffuse large B-cell lymphoma in HIV-positive patient - Oliveira, Marina Reis [UNESP]; Fernandes, Darcy [UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP]; De Andrade, Cleverton Roberto [UNESP]; Navarro, Cláudia Maria [UNESP]; Pereira-Filho, Valfrido Antonio [UNESP] (Wolters Kluwer, 2016)
This article describes the occurrence of diffuse large B-cell lymphoma in a 39-year-old humanimmunodeficiency virus-positive patient. The patient sought medical care complaining of increased volume in the right mandibular angle and imaging tests showed an extensive radiolucency with undefined boundaries compromising the mandibular border. After the incisional biopsy, the patient had a pathological fracture in the region, which was properly treated in a second surgical procedure using a 2.4-mm reconstruction plate. Immunohistochemical analysis revealed positive marking for CD3, CD79a, Ki67, and Epstein-Barr virus-encoded RNA. The treatment consisted of concurrent antiretroviral therapy with chemotherapy with rituximab combined with cyclophosphamide, doxorubicin, vincristine, and prednisone. Examinations of images (2 years postoperatively) revealed complete bone repair and absence of injury recurrence. This work is important because it describes an unusual location of diffuse large B-cell lymphoma and shows the importance of diagnosis and treatment of the injury at an early stage in order to promote the prognosis and survival of patients.
Keywords: Diffuse large B-cell lymphoma; Human immunodeficiency virus; Non-Hodgkin lymphoma; Pathological mandibular fracture